INCENTIVE INEQUALITIES AND FREEDOM OF OCCUPATIONAL CHOICE. (16th July 2015) - Mackay, Douglas
Abstract: In Rescuing Justice and Equality, G.A. Cohen argues that the incentive inequalities permitted by John Rawls's difference principle are unjust since people cannot justify them to their fellow citizens. I argue that citizens of a Rawlsian society can justify their acceptance of a wide range of incentive inequalities to their fellow citizens. They can do so because they possess the right to freedom of occupational choice, and are permitted – as a matter of justice – to exercise this right by making occupational decisions on the basis of a wide range of values and preferences.